Nickel-based catalyst for preparing photoresponse polymer by catalyzing ethylene copolymerization as well as preparation method and application of nickel-based catalyst
The preparation of a nickel catalyst to catalyze the copolymerization of ethylene and acrylate monomers solves the problem of preparing photoresponsive polymers in the prior art, realizes the performance change of the material under light stimulation, improves the interfacial adhesion and hydrophilicity, and expands the application field.
Patent Information
- Application Number
- CN202511020734.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-12-16
Smart Images

Figure CN121135786A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalytic olefin polymerization technology, specifically to a nickel-based catalyst for the catalytic copolymerization of ethylene to prepare photoresponsive polymers, its preparation method, and its application. Background Technology
[0002] Polyolefins are among the most important polymer materials affecting human production and life, accounting for more than half of global plastic production. As simple hydrocarbons, polyolefins require additional chemical modifications or functional additives to endow them with customized functions. Recent research in the development of functional polyolefins has moved beyond traditional methods that simply improve surface properties by incorporating polar moieties. The creation of customized functionalized polyolefins using specific functional units is receiving increasing attention. By introducing comonomers that respond to stimuli such as light, heat, mechanical force, and chemical reagents, complex functional polyolefins with unique properties and applications can be prepared.
[0003] Photoresponsive intelligent polymer systems exhibit multi-dimensional functional advantages due to their unique molecular design characteristics. These materials achieve directional conversion of light energy into mechanical energy / chemical energy by precisely constructing photoactive building blocks (such as azobenzene, spiropyran, etc.) and chemical coupling with the polymer skeleton. Their core advantages are reflected in: (1) precise dynamic response; (2) reversible switching of multiple stable states; (3) functional integration compatibility; (4) enhanced environmental adaptability; and (5) diverse preparation processes: photoactive building blocks can be controllably grafted through various methods such as free radical polymerization and ring-opening metathesis polymerization (ROMP), and post-functionalization modification (such as click chemistry) can further extend the response wavelength range of the material to the near-infrared region. Summary of the Invention
[0004] The technical problem to be solved by this invention is how to prepare a nickel-based catalyst to catalyze the copolymerization reaction of ethylene with various acrylate monomers, thereby preparing copolymers that can respond to external light stimulation and thus improve the performance of the materials.
[0005] The present invention solves the above-mentioned technical problems through the following technical means: The first aspect of this invention provides a method for preparing a nickel catalyst, comprising the following steps: Under strictly controlled humidity and oxygen conditions, functionalized phosphonol ligands were coordinated with pyridinemethyl nickel precursors. The coordination process of the metal center was controlled by stepwise feeding. After solid-liquid separation, the reaction mixture was purified by gradient crystallization using a mixed solvent system to obtain a high-purity nickel complex catalyst.
[0006] A second aspect of the present invention provides a nickel catalyst prepared using the above method.
[0007] A third aspect of this invention proposes the application of a nickel catalyst prepared by the above method in olefin polymerization reactions.
[0008] A nickel catalyst, the structure of which is shown below. .
[0009] The method for preparing the nickel catalyst, and the catalyst preparation route are as follows: .
[0010] As a preferred embodiment of the present invention, the method for preparing the nickel catalyst is characterized by comprising, under strictly controlled humidity and oxygen conditions, carrying out a coordination reaction between a functionalized phosphonophenol ligand and a pyridinemethyl nickel precursor, controlling the coordination process of the metal center by stepwise feeding, and after solid-liquid separation of the reaction mixture, recrystallizing with n-hexane to obtain a high-purity nickel complex catalyst.
[0011] As a preferred embodiment of the present invention, the strict humidity and oxygen control conditions are a temperature of 25-28°C and an oxygen content of less than 10 ppm.
[0012] As a preferred embodiment of the present invention, the molar ratio of the functionalized phosphonophenol ligand to the pyridine methyl nickel precursor is 1:1.1.
[0013] The application of the nickel catalyst in the catalytic copolymerization of olefins to prepare photoresponsive polymers.
[0014] A method for preparing photoresponsive polymers by copolymerization of olefins catalyzed by a nickel catalyst includes the following steps: S1: In a glove box, add the catalyst, polar monomer, and organic solvent as described in claim 1 to the reaction vessel to dissolve them, add a co-catalyst, seal the reaction vessel and remove it, heat it up and inject ethylene, and stir the reaction. S2: After termination, precipitate the polymer, wash and dry it, and store it in a dark place.
[0015] As a preferred embodiment of the present invention, the polar monomer is selected from benzoyl acrylate, 1-naphthyl acetate, dimethyl phenyl acrylate, or diphenylbicyclo[2.2.1]heptane-2,3-dicarboxylate.
[0016] As a preferred embodiment of the present invention, the organic solvent is one or more selected from petroleum ether, pentane, hexane, heptane, octane, hydrogenated gasoline, isoalkanes, methylcyclohexane, decahydronaphthalene, methylcyclohexane, cyclohexane, benzene, toluene, xylene, saturated isoalkanes, hydrogenated gasoline, dichloromethane, chloroform, chlorobenzene, and dichlorobenzene.
[0017] As a preferred embodiment of the present invention, the co-catalyst is one or more selected from diethylaluminum chloride, methylaluminoxane, ethylaluminum dichloride, triisobutylaluminum, and tris(pentafluorophenyl)boron.
[0018] Beneficial Effects: This invention synthesizes photoresponsive functionalized polyolefin materials by copolymerizing ethylene with acrylate monomers using a phosphonophenol nickel catalyst with electronically modulated effects. The topological structure of the polymer can be controlled by external light stimulation or by selecting different monomers. Polar monomers include benzoyl acrylate, 1-naphthalene acetate, dimethyl phenyl 2,6-acrylate, and diphenylbicyclo[2.2.1]heptane-2,3-dicarboxylate. The material properties of copolymers containing different monomers before and after light irradiation were studied by irradiating them with ultraviolet light of a certain wavelength and sunlight. This photoresponsive polymer exhibits unique characteristics during the property transformation process. While the material retains the original characteristics of polyethylene (good flexibility, chemical stability, and certain mechanical strength, etc.) internally, its surface simultaneously possesses good interfacial adhesion, good hydrophilicity, and excellent dyeability. This unique combination of properties makes the photoresponsive polymer show important research value and application potential in the field of materials science. This strategy enables the controllable preparation of photoresponsive functionalized polyolefins.
[0019] 2. A photoresponsive monomer coordination copolymerization method based on the classic phosphonophenol-nickel catalytic system was used to achieve copolymerization of ethylene and a photosensitive monomer (benzoyl acrylate) by controlling the material's topology through photostimulation response. Ultraviolet light (245 nm) irradiation triggered photo-Fries rearrangement on the material surface. ATR-IR analysis confirmed the transformation of the ester group to an ortho-hydroxy aromatic ketone structure. Contact angle testing showed that the material's wettability changed from hydrophobic to hydrophilic, and the adhesion between the material and the metal plate was enhanced, increasing to 178.7 N with a displacement of 10 mm.
[0020] 3. The copolymer obtained by this invention can combine well with dyes in terms of dyeing performance, making the dyeing process more uniform and firm, which provides a broad prospect for its application in textile, printing and dyeing and other industries.
[0021] 4. The copolymer obtained in this invention exhibits a significant change in surface hydrophilicity, with the photoresponsive polymer showing a substantial increase in surface affinity for water. This characteristic is crucial for many applications requiring contact with aqueous media or good wettability, such as tissue engineering scaffolds and drug delivery carriers in the biomedical field. Furthermore, the material's adhesion is also effectively improved, giving this polymer potential applications in adhesives, coatings, and other fields.
[0022] 5. Photoresponsive intelligent polymer systems exhibit multi-dimensional functional advantages due to their unique molecular design characteristics. These materials achieve directional conversion of light energy to mechanical energy / chemical energy by precisely constructing photoactive building blocks (such as azobenzene, spiropyran, etc.) and chemical coupling with the polymer skeleton. Their core advantages are reflected in: (1) accurate dynamic response (2) reversible switching of multiple stable states (3) functional integration compatibility (4) enhanced environmental adaptability (5) diverse preparation processes: photoactive building blocks can be controllably grafted through various methods such as free radical polymerization and ring-opening metathesis polymerization (ROMP), and post-functionalization modification (such as click chemistry) can further extend the response wavelength range of the material to the near-infrared region. Attached Figure Description Figure 1 The synthetic route diagram for monomer M2 prepared in Example 3; Figure 2 The synthetic route diagram for monomer M3 prepared in Example 4; Figure 3 The synthetic route diagram for monomer M4 prepared in Example 5; Figure 4 The 1H NMR spectrum of monomer M2 prepared in Example 3; Figure 5 The 1H NMR spectrum of monomer M3 prepared in Example 4; Figure 6 The hydrogen NMR spectrum of monomer M4 prepared in Example 5; Figure 7 The synthesis route of the catalyst Ni1 prepared in Example 1 is shown below; Figure 8 The 1H NMR spectrum of ligand L1 prepared in Example 1; Figure 9 This is a schematic diagram of the photo-Fries rearrangement of monomer M2 prepared in Example 3; Figure 10 Comparison of polymer infrared spectra of samples 1, 2, 3, and 4 prepared in Application Example 10; Figure 11 Comparison of UV spectra of staining reaction of sample 4 prepared in application example 10: after light irradiation (1), before light irradiation (2); Figure 12 The graph shows a comparison of the metal adhesion force of the polymer before and after light irradiation for samples 3 and 4 prepared in Application Example 10. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] In the method of the present invention, the nickel-based catalyst used as the starting material can be any nickel-based catalyst known in the art, which can be commercially available or conveniently prepared by methods known in the art.
[0025] Example 1: For ease of description, the structure is as follows: The phosphonophenol nickel catalyst, named Ni1, was synthesized according to the literature (ACS Catal. 2018, 8, 5963−5976.).
[0026] The preparation method of compound 1a includes the following steps: Under a nitrogen atmosphere, tert-butylphenol and 0.5 eq. of p-toluenesulfonic acid were dissolved in dry DCM. Then, 1.1 eq. of pyran solution was added, and the mixture was stirred overnight at 25-28°C. The reaction product was extracted and dried. Excess solvent was removed by vacuum evaporation. Column chromatography was used for further purification to obtain the target product.
[0027] The method for synthesizing ligand L1 includes the following steps: In a Schlenk flask equipped with a purging gas, the product synthesized in the previous step (compound 1a) was dissolved in a dry tetrahydrofuran solution. 1.1 eq. n-BuLi (1.6 M in THF) was slowly added dropwise at 0°C, and the solution was allowed to react for 5 hours; this is denoted as reaction C. Subsequently, the synthesized P-Cl ligand was added to another Schlenk flask under a nitrogen atmosphere. It was dissolved in dry THF and denoted as reaction D. Reaction D was slowly added dropwise to reaction C under anhydrous and oxygen-free conditions, and the solution was slowly heated overnight. After the reaction was complete, the solution was quenched (to remove any remaining n-BuLi). The solution was extracted and dried. The solvent was removed by vacuum distillation, and the residue was purified by column chromatography to obtain a white product. The product was dried to constant weight in a vacuum drying oven and stored under an inert gas atmosphere.
[0028] The synthesis and purification of catalysts include the following steps: Under strictly controlled humidity and oxygen conditions (temperature 25-28℃, oxygen content below 10ppm), a coordination reaction was carried out between a functionalized phosphonophenol ligand (ligand L1) and a pyridinemethyl nickel precursor (synthesized according to the literature ACS Catal. 2018, 8, 5963−5976). The molar ratio of L1 to the pyridinemethyl nickel precursor was 1.1:1. To control the coordination process of the metal center, the functionalized phosphonophenol ligand (ligand L1, 1 eq) was dissolved in an appropriate amount of anhydrous toluene under a N2 atmosphere, and then the pyridinemethyl nickel precursor (1.1 eq) was added in batches. The mixture was stirred for 3 h, and after solid-liquid separation, the reaction mixture was recrystallized from n-hexane to obtain a high-purity nickel complex catalyst. The product was stored under a nitrogen-protected environment.
[0029] Example 2: Monomer 1 (benzoyl acrylate) was purchased directly and dried with anhydrous copper sulfate before use. For ease of description, it is named M1.
[0030] Example 3: According to the method described in the literature
[72] , monomer 2 (1-naphthyl acetate) was prepared by dissolving 1 eq. of 1-naphthol in dry dichloromethane under a nitrogen atmosphere, adding 1 eq. of triethylamine, reacting at 0°C for 10 minutes, then slowly adding 1.5 eq. of acryloyl chloride (diluted with three times the volume of dichloromethane), and then slowly raising the solution to room temperature and reacting overnight. Excess acryloyl chloride was quenched with saturated brine. Liquid-liquid extraction was performed using dichloromethane. The combined organic phases were washed successively with saturated sodium carbonate solution and brine, and dried over anhydrous sodium sulfate for 6 h. One percent of polymerization inhibitor (2,6-di-tert-butylphenol, to prevent free radical self-polymerization in the product) was added, the solvent was removed by vacuum distillation, and the residue was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate) to obtain a white oily product (yield 60%). The product was dried under vacuum in a double-row tube to remove residual solvent. It was stored under inert gas at low temperature and protected from light. For ease of description, it will be named M2.
[0031] Example 4: The synthesis steps for monomer 3 (dimethylphenyl 2,6-acrylate) were the same as those for monomer 2 (naphthyl acetate). 1 eq. of 2,6-dimethylphenol was added to replace the 1-naphthol in Example 3, and the rest of the procedure was the same. A white oily product (70%) was obtained, which, for ease of description, is named M3.
[0032] Example 5: The synthesis of monomer 4 (diphenylbicyclo[2.2.1]heptane-2,3-dicarboxylate) was carried out according to the method described in the literature
[121] . The synthesis of monomer 4 was carried out in two steps under a nitrogen atmosphere. Step 1: 1 eq. of norbornyl ediol was dissolved in dry DCM and reacted in ice water for 10 minutes. 2.3 eq. of oxalyl chloride and a few drops of DMF were slowly added dropwise as catalysts for the reaction system. A large amount of gas was produced in the reaction. After no more gas was generated in the flask, the excess oxalyl chloride was removed under vacuum after 1 hour of reaction.
[0033] Step 2: Under strictly anhydrous and oxygen-free conditions, 2.3 eq. of phenol and 3 eq. of triethylamine (to neutralize the acidity of the system during the reaction) were dissolved in dry dichloromethane and denoted as product B. The product synthesized in step 1 was dissolved in dry DCM under a nitrogen atmosphere and stirred for 10 minutes and denoted as product A. Under anhydrous and oxygen-free conditions at 0°C, product B was slowly added dropwise to product A, and the temperature was slowly increased overnight. Liquid-liquid extraction was performed using dichloromethane. The combined organic phases were washed successively with saturated sodium carbonate solution and brine, and dried over anhydrous sodium sulfate for 6 h. One percent of a polymerization inhibitor (2,6-di-tert-butylphenol, to prevent free radical self-polymerization in the product) was added, the solvent was removed by vacuum distillation, and the residue was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate). The target product was a white solid (60% yield). It was dried to constant weight in a vacuum drying oven. It was stored under inert gas at low temperature and protected from light. For ease of description, it is named: M4.
[0034] Application Example 1: Ethylene copolymerization using nickel-based catalysts and polar monomers (1) Copolymerization of ethylene with monomers Weigh 10 μmol of catalyst into the glove box and dissolve it completely in 3 mL of toluene. Draw the catalyst out using a syringe. Weigh a certain concentration of comonomer M1 (obtained by drying and filtering anhydrous copper sulfate) and dissolve it in a certain amount of n-heptane (to better dilute the monomer before injecting it into the polymerization flask), so that the total volume of reaction solvent required for polymerization is 50 mL, and the final concentration of M1 in the system is 2 mol / L. Add 0.2 mL of triisobutylaluminum co-catalyst to remove residual water from the polymerization system. Then add the remaining volume of n-heptane solvent and a stir bar. After a thorough sealing, remove the syringe containing the catalyst from the glove box and install it on a magnetic stirring platform equipped with a constant-temperature oil bath. Connect the ethylene pipeline and gradually raise the temperature to 50°C. Once the temperature stabilizes, inject 8 atmospheres of ethylene gas into the system and maintain the baseline pressure. Completely remove residual gas from the pipeline through three vacuum-gas-purging cycles. Then add the catalyst into the flask and rapidly increase the system pressure to the reaction pressure. After the reaction is terminated after 1 hour, the pressure is gradually released, the reactor is opened and a precipitant is added to precipitate the polymer. After solid-liquid separation, washing and vacuum drying, the target product is obtained. The product must be stored in a light-protected environment.
[0035] (2) Material post-processing: The dried polymer was weighed and calculated. The product was first extracted using a Soxhlet extractor with methanol as the extraction solvent and refluxed at 100°C for three days to remove any unreacted monomers remaining in the copolymer. The extracted product was then placed in a drying oven to dry and store away from light.
[0036] (3) Staining reaction treatment: The copolymer was prepared into a polymer matrix film of a certain size by hot pressing.
[0037] (1) Preparation of staining solution: Accurately weigh 20 mg of indigo (98%) (accurate to 0.01 mg), dissolve it in 20 mL of tetrahydrofuran (THF, HPLC grade) that has been dehydrated by molecular sieve, and disperse it with ultrasonic assistance until it is completely dissolved to obtain a staining solution with a concentration of 2.00 mg / mL; (2) Surface dyeing treatment: The pre-made film (1.5 cm × 1.5 cm) that has not been exposed to light and has been exposed to ultraviolet light for 6 h is immersed in the dyeing solution and placed in a constant temperature magnetic stirring reactor. The reaction temperature is maintained at 60±1℃ and the stirring is continued for 3 h.
[0038] (3) Post-processing: Remove the dyed film and rinse it three times each with anhydrous methanol and acetone to ensure complete coloring. Place it in a vacuum drying oven and dry it to constant weight. Finally, a yellow film is obtained and stored in the dark for ultraviolet spectroscopy testing.
[0039] The results are summarized in Table 1 below.
[0040] Application Example 2: Ethylene copolymerization using a nickel-based catalyst and polar monomer M1 The difference between Application Example 2 and Application Example 1 is that the temperature of 50℃ is replaced with 70℃, while the other steps are the same as in Application Example 1. The results are summarized in Table 1 below.
[0041] Application Example 3: Ethylene copolymerization using a nickel-based catalyst and polar monomer M1 The difference between Application Example 3 and Application Example 1 is that the polymerization solvent n-heptane was replaced with toluene, and Application Example 1 was repeated at 50°C and 70°C, respectively. The results are summarized in Table 1 below.
[0042] Application Example 4: Ethylene copolymerization using a nickel-based catalyst and polar monomer M2 The difference between Application Example 4 and Application Example 1 is that "monomer M2 of Example 3" was used instead of "monomer M1 of Example 1", and Application Example 1 was repeated at 50°C and 70°C respectively. The results are summarized in Table 1 below.
[0043] Application Example 5: Ethylene copolymerization using a nickel-based catalyst and polar monomer M2 The difference between Application Example 5 and Application Example 1 is that "monomer M2 of Example 3" was used instead of "monomer M1 of Example 1", and the polymerization solvent n-heptane was replaced with toluene. Application Example 1 was repeated at 50°C and 70°C, respectively. The results are summarized in Table 1 below.
[0044] Application Example 6: Ethylene copolymerization using a nickel-based catalyst and polar monomer M3 The difference between Application Example 6 and Application Example 1 is that "monomer M3 of Example 4" was used instead of "monomer M1 of Example 1", and Application Example 1 was repeated at 50°C and 70°C respectively. The results are summarized in Table 1 below.
[0045] Application Example 7: Ethylene copolymerization using a nickel-based catalyst and polar monomer M3 The difference between Application Example 7 and Application Example 1 is that "monomer M3 of Example 4" was used instead of "monomer M1 of Example 1", and the polymerization solvent n-heptane was replaced with toluene. Application Example 1 was repeated at 50°C and 70°C, respectively. The results are summarized in Table 1 below.
[0046] Application Example 8: Ethylene copolymerization using a nickel-based catalyst and polar monomer M4 The difference between Application Example 8 and Application Example 1 is that "monomer M4 of Example 5" was used instead of "monomer M1 of Example 1", and Application Example 1 was repeated at 50°C and 70°C respectively. The results are summarized in Table 1 below.
[0047] Application Example 9: Ethylene copolymerization using a nickel-based catalyst and polar monomer M4 The difference between Application Example 9 and Application Example 1 is that "monomer M4 of Example 5" was used instead of "monomer M1 of Example 1", and the polymerization solvent n-heptane was replaced with toluene. Application Example 1 was repeated at 50°C and 70°C, respectively. The results are summarized in Table 1 below.
[0048] Application Example 10: Ethylene copolymerization using a nickel-based catalyst and monomers M1, M2, M3, and M4 that have been exposed to 254 nm ultraviolet light and sunlight. Using an ATR-IR infrared spectrometer, monomers M1, M2, M3, and M4 from Examples 2-5 were irradiated with 254 nm ultraviolet light and then with sunlight for 6 hours. The irradiated monomers were then used to replace monomer M1 from Example 1, and the other steps were the same as in Application Example 1. For ease of description, they are named Sample 1, Sample 2, Sample 3, and Sample 4.
[0049] Table 1. Data on the copolymerization of ethylene with polar monomers catalyzed by nickel catalyst. a aReaction conditions: 10 µmol catalyst, 50 mL heptane and monomer, 60 min reaction time, and 8 atm reaction pressure. b Activity in kg·mol -1 ·h -1 Units. c DSC is a secondary heating method. d M n The unit is kg·mol. -1 , M n and M w / M n Determined in 1,2,4-trichlorobenzene at 160 °C by gel permeation chromatography (GPC).
[0050] In the copolymerization of ethylene, different acrylate monomers were selected to react with ethylene. Acrylate monomers can self-polymerize and copolymerize with other monomers, and are the most important raw materials in the production of adhesives, synthetic resins, and the manufacture of specialty rubbers and plastics. Acrylate rubber, produced using acrylates as raw materials, occupies an important position in the market. However, self-polymerized acrylate products have disadvantages such as poor cold resistance and poor resistance to water and water vapor. Based on these shortcomings, a phosphorophenol-nickel catalyst was further synthesized to catalyze the copolymerization reaction of ethylene and acrylate monomers.
[0051] Table 1 shows that polymerization reactions were first carried out at 50℃ and 70℃ respectively, and the activity of the same monomer differed at the two temperatures. The classic phosphonophenol-nickel catalyst exhibited the best activity at lower temperatures in the homopolymerization of ethylene. Therefore, the polymer obtained at 50℃ showed higher activity than that obtained at 70℃. The copolymerization activity of olefins is affected by various factors, among which the choice of solvent is crucial. Therefore, different solvents were used in this system for the polymerization reaction. Toluene and n-heptane were selected as solvents. The copolymer obtained with toluene as the solvent showed significantly higher activity than that with n-heptane. This is because toluene is a polar solvent, which has less impact on polar monomers, thus resulting in higher reactivity. n-Heptane, as a non-polar solvent, is unfavorable for the polymerization of polar monomers with ethylene, resulting in lower copolymerization activity. However, n-heptane has low toxicity and is relatively safe for production applications, and is usually given priority in material manufacturing.
[0052] The polymers obtained in corresponding use cases 1-9 were subjected to surface water contact angle testing, infrared testing, dyeing reaction testing, and adhesion testing. The test results are shown in Table 2 and... Figure 10-12 .
[0053] Table 2 shows the water contact angle test data of the polymers prepared in Examples 1-9 of this invention; Figure 10 Comparison of polymer infrared spectra of samples 1, 2, 3, and 4 prepared in Application Example 10; Figure 11 Comparison of UV spectra of staining reaction of sample 4 prepared in application example 10: after light irradiation (1), before light irradiation (2); Figure 12 The graph shows a comparison of the metal adhesion force of the polymer before and after light irradiation for samples 3 and 4 prepared in Application Example 10.
[0054] As shown in Table 2, before illumination, the surface of the material exhibits a contact angle (WCA) greater than 90°, indicating a hydrophobic state. After prolonged exposure to 254nm ultraviolet light and sunlight, the WCA angle is less than 90°.
[0055] The change in the contact angle is due to the fact that before light irradiation, the ester group is a branched functional group of the material. After exposure to ultraviolet light and sunlight, the surface functional groups undergo photo-Fries rearrangement, and the hydroxyl group becomes a hydrophilic group, so the WCA (water contact angle) is significantly reduced after light irradiation. In order to avoid the oxidation of the polymer surface due to prolonged light irradiation, which would also reduce the water contact angle and cause hydrophilicity, light treatment tests were also performed on LDPE, HDPE and LLDPE. According to (Table 2S, Entries 15-17), it can be observed that there is no change in the water contact angle after ultraviolet light irradiation (254 nm, 6 h).
[0056] Table 2 Water contact angle test data a a Conditions: The test was conducted using a film of equal thickness, 0.3 mm, and the water used was deionized water.
[0057] b This is the water contact angle measured without light exposure.
[0058] c Irradiate with ultraviolet light (254 nm) for 6 h.
[0059] d Exposure to sunlight for 6 hours.
[0060] Figure 10 The infrared spectra of polymer samples 1, 2, 3 and 4 prepared in Application Example 10 of this invention are shown. By analyzing the test results, the changes that occurred on the surface of the copolymer were confirmed by the specific chemical reaction phenomenon, namely, the photo-Fries rearrangement of ester groups under light irradiation, which is then converted into the main ortho-rearrangement product hydroxy aromatic ketone [108-115].
[0061] At 3200-3500 cm -1 Within this specific wavenumber range, a completely new vibration zone appears ( Figure 10 The characteristic peak of the hydroxyl group on the benzene ring is located exactly at 3200-3500 cm⁻¹. -1 The appearance of the infrared characteristic peak at this position indicates that a photo-Fries rearrangement reaction occurred on the material surface under the stimulation of light. During this reaction, the ester groups originally present in the material undergo a photochemical reaction of Fries rearrangement to generate the corresponding ortho-product hydroxyl ketone, meaning the polymer surface structure has changed. To avoid oxidation of the polymer surface due to prolonged light exposure, the infrared peak is positioned at the same vibrational location. Infrared measurements were also performed on LDPE samples after light treatment, according to (…). Figure 10 It can be observed that no new vibrational bands are generated under ultraviolet light (254 nm, 6 h).
[0062] Figure 11 The UV spectrum of polymer sample 4 in Application Example 10 was used to verify whether the dyeing effect of the copolymer after light irradiation conforms to the characteristic of surface property changes caused by changes in material structure. UV-Vis diffuse reflectance spectroscopy analysis was used. Air was scanned as a control for UV testing, with the UV scanning wavelength range of 200-700 nm, and reflectance was obtained at 1 nm intervals. The light reflectance of the sample was measured at each wavelength, and a test curve was obtained by comparing wavelength and spectral reflectance. A larger K / S value (where K and S represent the spectral absorption and scattering coefficients, respectively) indicates higher color intensity. Pure PE has a very small K / S value due to the non-polar nature of polyethylene and its correspondingly lower compatibility with highly polar dye molecules. Firstly, the UV absorption curve clearly shows that the material irradiated with UV light absorbs UV light better, while the unirradiated material absorbs less light. The color intensity of the extracted copolymer was determined using the Kubelka-Munk equation. In this equation, K and S represent the spectral absorption and scattering coefficients, respectively.
[0063] The minimum reflectance of the unexposed material is 18.9, with a K / S value of 8.47. The minimum reflectance of the exposed material is 28.8, with a K / S value of 13.4. Hydroxyl groups can effectively increase the affinity of polymer materials for dye molecules; therefore, the dyeing performance of the exposed material is significantly improved.
[0064] To test the adhesion properties of the polymer material, an overlap shear test was designed and conducted. Stainless steel sheet was chosen as the test material to study the polymer material's ability to adhere to metals. Stainless steel, as a common and representative metallic material, has surface properties that have broad reference value in industrial applications.
[0065] The specific experimental procedure is as follows: The polymer material to be tested is precisely placed in the middle of the overlapping contact area of two stainless steel plates. To ensure the accuracy and consistency of the experimental data, the contact area between the polymer and the steel plates is strictly controlled. The steel plates are set to be 60 mm in length and 22 mm in width, while the sample width is 8.87 mm and the thickness is 0.36 mm. Subsequently, the steel plates and the polymer material are heated. The purpose of this heating process is to enable the polymer material to smoothly and firmly connect the two steel plates through its own physical changes without the need for additional external pressure, thereby simulating the adhesion process of materials in actual application scenarios.
[0066] After specimen preparation, a universal testing machine was used to perform tensile tests on the specimens. The universal testing machine can accurately measure the force borne by the specimen and the corresponding displacement changes during the tensile process. Through the collation and analysis of the test data, the adhesion performance of the polymer material under light exposure conditions was presented intuitively in the form of charts.
[0067] The specific data on the metal adhesion force of samples 3 and 4 before and after light irradiation show that: the unirradiated polymer sample 3 has a tested adhesion force of 149.7 N and a corresponding displacement of 9.36 mm; after being irradiated with ultraviolet light at a wavelength of 254 nm, the adhesion force of the polymer increases to 178.7 N, and the displacement reaches 10 mm. Figure 12 The unirradiated polymer sample 4 showed an adhesive strength of 148 N and a displacement of 9.37 mm; after irradiation with 254 nm ultraviolet light, the adhesive strength increased to 194.5 N and the displacement reached 10.42 mm. Figure 12 As can be clearly and intuitively observed from the charts, the adhesion of the polymer treated with light is significantly improved compared to the untreated polymer. The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nickel catalyst, characterized in that, The structure is as follows 2. The method for preparing the nickel catalyst according to claim 1, characterized in that, The catalyst preparation route is as follows:
3. The method for preparing the nickel catalyst according to claim 2, characterized in that, This includes conducting a coordination reaction between functionalized phosphonol ligands and pyridine methyl nickel precursors under strictly controlled humidity and oxygen conditions. The coordination process of the metal center is controlled by stepwise feeding. After solid-liquid separation, the reaction mixture is recrystallized with n-hexane to obtain a high-purity nickel complex catalyst.
4. The preparation method according to claim 1, characterized in that, The strict humidity and oxygen control conditions are a temperature of 25-28℃ and an oxygen content of less than 10ppm.
5. The preparation method according to claim 1, characterized in that, The molar ratio of the functionalized phosphonophenol ligand to the pyridine methyl nickel precursor was 1:1.
1.
6. The application of the nickel catalyst according to claim 1 in the catalytic copolymerization of olefins to prepare photoresponsive polymers.
7. A method for preparing photoresponsive polymers by copolymerization of olefins catalyzed by a nickel catalyst according to claim 1, characterized in that, Includes the following steps: S1: In a glove box, add the catalyst, polar monomer, and organic solvent as described in claim 1 to the reaction vessel to dissolve them, add a co-catalyst, seal the reaction vessel and remove it, heat it up and inject ethylene, and stir the reaction. S2: After termination, precipitate the polymer, wash and dry it, and store it in a dark place.
8. The method according to claim 7, characterized in that, The polar monomer is selected from benzoyl acrylate, 1-naphthyl acetate, dimethyl phenyl acrylate, or diphenylbicyclo[2.2.1]heptane-2,3-dicarboxylate.
9. The method according to claim 7, characterized in that, The organic solvents are all one or more selected from petroleum ether, pentane, hexane, heptane, octane, hydrogenated gasoline, isoalkanes, methylcyclohexane, decahydronaphthalene, methylcyclohexane, cyclohexane, benzene, toluene, xylene, saturated isoalkanes, hydrogenated gasoline, dichloromethane, chloroform, chlorobenzene, and dichlorobenzene.
10. The method according to claim 7, characterized in that, The co-catalysts are all one or more selected from diethylaluminum chloride, methylaluminoxane, ethylaluminum dichloride, triisobutylaluminum, and tris(pentafluorophenyl)boron.